Puss’ Anxiety and Defense Mechanism in The Puss In Boots: The Last Wish Movie - Nurcahya, Radhitya; Juanda, Juanda (Mahadaya: Jurnal Bahasa, Sastra, Dan Budaya, 2024)
The purpose of this study is to investigate the ways of anxiety and defense mechanisms work on the character Puss in the Puss in Boots: The Last Wish (2022) movie through the theory of anxiety and defense mechanisms by Freud. By employing a descriptive qualitative approach and the theory of literary psychology, this study aims to understand how to read and interpret a literary work from a psychological perspective. The data used are the scenes and dialogues of Puss from the film. The results show that Puss experienced three types of anxieties which are realistic, moral and neurotic anxieties, and five types of defense mechanisms namely, denial, displacement, rationalization, reaction formation, and repression. Keywords: Anxiety, Defense Mechanism, Impulse, Freudian Theory